PENGARUH SISTEM PELACAKAN BERBASIS WEBSITE, KUALITAS LAYANAN LOGISTIK DAN PENANGANAN KOMPLAIN TERHADAP KEPUASAN PELANGGAN : (Studi Pada JNE di Kabupaten Majalengka) - Nining Kurniasih (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2022)
Abstract. The growth and development of a country's economy is in dire need of reliable transportation facilities and infrastructure. Delivery services are part of the needs of consumers who tend to want something that is easy, fast, safe and practical in all matters of shipping goods. One way to overcome this, companies in the service sector provide a website-based tracking system and logistics services. If a problem occurs, is willing to handle complaints from customers to achieve customer satisfaction. This study aims to determine the effect of webiste-based tracking systems, logistics service quality and complaint handling on customer satisfaction. This research uses descriptive analysis and verification methods. The data collection technique used is by distributing questionnaires. The population in this study were JNE customers in Majalengka Regency with a sample of 100 respondents. The sampling technique used is incidental sampling. This study uses a Likert scale. Data analysis using classical assumption test, multiple regression analysis, coefficient of determination analysis, model feasibility test and hypothesis testing with partial test. The results of the research that have been carried out show that website-based tracking systems affect customer satisfaction, logistics service quality affects customer satisfaction, and complaint handling affects customer satisfaction.